Despite crises, the stability of the euro is rooted in the middle class - Christian Bayer; Alexander Kriwoluzky; Gernot J. Müller; Fabian Seyrich (DIW Weekly Report, 2023)
In the 24 years since its introduction, the euro has experienced a financial crisis, a government debt crisis, a global pandemic, and an energy crisis-and survived. Using a model focusing on households, this Weekly Report shows that the monetary union's stability is rooted in the fact that the middle class neither gains nor loses significantly relative to an independent currency following business cycle impulses. The shifting of the costs due to a crisis as a result of membership in a monetary union occurs at the tails of the wealth distribution, namely between groups of equal wealth in different countries.
Keywords: F45; E52; D31; 330; HANK2; OCA theory; Two-country model; monetary union; spillovers; monetary policy; household heterogeneity; inequality; households